Proyeksi Produk Domestik Regional Bruto (PDRB) Di Kabupaten Aceh Tamiang Menggunakan Trend Parabolik - Labora Febriyanti Lumban Toruan Lumban Toruan; Ulya Nabilla (Program Studi Matematika, Fakultas Teknik, Universitas Samudra. Langsa, Aceh., 2022)
Gross Regional Domestic Product is the added value generated by all economic units in a certain area. GRDP in Aceh Tamiang Regency has increased every year, but needs to be increased again to conform to national standards. Therefore, it is necessary to know the amount of GRDP in the future in Aceh Tamiang Regency. The purpose of this study is to determine the effectiveness of the Parabolic Trend Method in projecting GRDP in Aceh Tamiang Regency and to find out the results of GRDP in Aceh Tamiang Regency from 2022 to 2024. used is secondary data, namely the amount of GRDP obtained from the office of the Central Statistics Agency (BPS) of Aceh Tamiang Regency in 2011 – 2021. The data obtained from the BPS of Aceh Tamiang Regency is projected using the Parabolic Trend method. Based on the projections carried out with a parabolic trend in the GRDP projection in Aceh Tamiang Regency, so that the total GRDP in Aceh Tamiang Regency in 2022 is 6,293,916.23, in 2023 it is 6,436,888.99 and in 2024 6,576. 024.55 with successively increasing percentages. This shows that from 2022 to 2024 the GRDP in Aceh Tamiang Regency has increased. Keywords: Projection, Gross Regional Domestic Product, Parabolic Trend.